Coding Theory Essentials - Harkut, Dinesh G.; Kasat, Kashmira N. (IntechOpen, 2023)
In an era where data is the lifeblood of our interconnected world, the ability to transmit and protect information is of paramount importance. Coding Theory Essentials is your comprehensive guide to understanding the fundamental principles and techniques that underpin the art of coding theory. This edited book brings together the expertise of leading researchers and practitioners to explore the intricate world of coding theory. From error-correcting codes to channel capacity, from block codes to convolutional codes, this collection covers a wide range of topics, providing both theoretical foundations and practical insights. Whether you are a computer scientist, an electrical engineer, or simply curious about the inner workings of information coding, this book offers a captivating journey into the heart of modern communication. Explore the elegant beauty of coding theory and unleash your potential to innovate within this exciting field. Join us on a quest to decode the secrets of coding theory and unleash the power of reliable communication. Coding Theory Essentials is a must-have resource for researchers, students, and practitioners seeking to navigate the complexities of our digital world. Open the book, unlock the knowledge, and embark on a transformative journey into the world of coding theory.